Shiraiaceae, new family of Pleosporales (Dothideomycetes, Ascomycota) - Liu, Yong-Xiang; Hyde, Kevin D; Ariyawansa, Hiran A; Li, Wen-Jing; Zhou, De-Qun; Yang, You-Lian; Chen, Yi-Meng; Liu, Zuo-Yi (Phytotaxa, 2013)
Shiraia bambusicola is an economically important medicinal fungus on bamboo. In this paper we re-describe the holotype and designate an epitype based on fresh specimens collected from Zhejiang Province in China. Morphological characters agree with those of the holotype and phylogenies based on combined partial LSU-rDNA, EF and RPB gene sequence data from the epitype, suggest that it is a new family of Pleosporales. The new family is introduced and the holotype and epitype are both illustrated.